Raman spectroscopy of serum: A study on 'pre' and 'post' breast adenocarcinoma resection in rat models. Issue 7 (15th July 2014) - Bhattacharjee, Tanmoy; Khan, Aarif; Kumar, Piyush; Ingle, Arvind; Maru, Girish; Krishna, C. Murali
Abstract : Risk of recurrence is a major problem in breast cancer management. Currently available prognostic markers have several disadvantages including low sensitivity and specificity, highlighting the need for new prognostic techniques. One of the candidate techniques is serum‐based Raman spectroscopy (RS). In this study, feasibility of using RS to distinguish 'pre' from 'post' breast tumor resection serum in rats was explored. Spectral analysis suggests change in proteins and amino acid profiles in 'post' compared to 'pre‐surgical' group. Principal‐Component‐Linear‐Discriminant‐Analysis shows 87% and 91% classification efficiency for 'pre' and 'post‐surgical' groups respectively. Thus, the study further supports efficacy of RS for theranostic applications.